2020
DOI: 10.3899/jrheum.201025
|View full text |Cite
|
Sign up to set email alerts
|

Increased Prevalence of Moderate to Severe Mitral and Aortic Valve Dysfunction in Systemic Sclerosis: A Case-control Study

Abstract: Objective To investigate the prevalence, severity and associated clinical factors of mitral and aortic valvular involvement in patients with systemic sclerosis (SSc). Methods This case–control study included 172 patients with SSc and 172 non-SSc adults without known cardiac disease matched by age, gender, and prevalence of cardiovascular risk factors. The screening of mitral and aortic valvular involvement was performed by transthoracic Doppler echocardiogram. The prevalence of aortic stenosis (AS) was also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is hypothesised that there is an increased frequency of valvular heart disease due to the effects of SSc itself; however, it remains unclear whether the observed increased rates of aortic and mitral valve disease seen in population-based studies [86] are attributable to the increased frequency of screening echocardiograms performed as part of routine SSc care. Case-control studies have suggested an increased frequency of moderate to severe aortic and mitral valvular disease in SSc [87,88]. However, valvular heart disease has not been linked with increased mortality [87] and how valvular pathology may impact SCD risk in SSc is unstudied.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesised that there is an increased frequency of valvular heart disease due to the effects of SSc itself; however, it remains unclear whether the observed increased rates of aortic and mitral valve disease seen in population-based studies [86] are attributable to the increased frequency of screening echocardiograms performed as part of routine SSc care. Case-control studies have suggested an increased frequency of moderate to severe aortic and mitral valvular disease in SSc [87,88]. However, valvular heart disease has not been linked with increased mortality [87] and how valvular pathology may impact SCD risk in SSc is unstudied.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…Case-control studies have suggested an increased frequency of moderate to severe aortic and mitral valvular disease in SSc [87,88]. However, valvular heart disease has not been linked with increased mortality [87] and how valvular pathology may impact SCD risk in SSc is unstudied.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…No meaningful associations were found between AS and psoriatic arthritis, Buerger's disease, gout, ankylosing spondylitis, or antiphospholipid antibody syndrome. Some of the inflammatory conditions in this study have been suggested to have associations with AS in very small studies or case reports, including rheumatoid arthritis [34], mixed connective tissue disease [35], and scleroderma (systemic sclerosis) [36] . For others, such as polyarteritis nodosa and Raynaud's syndrome, this is the first known identification of a relationship.…”
Section: Discussionmentioning
confidence: 85%
“…Another case-control study investigating the prevalence of MAVD in patients with SSc revealed that SSc patients have a significantly higher chance of experiencing moderate to severe MAVD compared to those without SSc, with a prevalence almost five times greater (OR 4.60) with MR being the most common lesion followed by AS and AR. On the other hand, the development of mitral stenosis is less frequent [ 6 ]. Aortic incompetence was documented with lesser frequency in the available literature.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic incompetence was documented with lesser frequency in the available literature. Narváez et al observed a notably higher occurrence of AR in individuals with SSc compared to control subjects [ 6 ]. Additionally, Fernández-Codina et al established a significant connection between AR and the limited skin subset of SSc [ 7 ].…”
Section: Discussionmentioning
confidence: 99%